Ipsilesional Impairments of Visual Awareness After Right-Hemispheric Stroke - Bonato, Mario; Romeo, Zaira; Blini, Elvio; Pitteri, Marco; Durgoni, Eugenia; Passarini, Laura; Meneghello, Francesca; Zorzi, Marco (Frontiers in Psychology, 2019)
Whether and how unilateral brain damage following stroke affects ipsilesional visuo-spatial processing is still poorly understood. Three main alternative hypotheses have been proposed, namely that ipsilesional processing is functionally i) hyperefficient, ii) impaired or iii) spared. Here we investigated the impact of concurrent information processing (i.e., multitasking) on ipsilesional space awareness. Twelve chronic right-hemisphere stroke patients with a total lack of awareness for the contralesional side of space were tested using a computerized experimental task that required spatial monitoring of two ipsilesional locations. Targets were presented immediately to the right of a central fixation mark (3° eccentricity), or farther to the right towards the screen edge (17° eccentricity), or on both locations. Target localization occurred either in isolation or while performing a concurrent visual or auditory task. Results showed that the most demanding condition occurred when two targets were simultaneously presented and patients were faced with additional task demands (in the visual or auditory modalities). In the context of concurrent visual load, ipsilesional targets presented at the rightmost location were omitted more frequently than those presented closer to fixation. This pattern qualifies ipsilesional processing in right-hemisphere stroke patients as functionally not normal.